1999
DOI: 10.1007/s002800050898
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis and antitumor efficacy of MKT-077, a novel antitumor agent

Abstract: MKT-077 (1-ethyl-2-[[3-ethyl-5-(3-methylbenzothiazolin-2-yliden)]-4- oxothiazolidin-2-ylidenemethyl] pyridinium chloride), a novel rhodacyanine dye in phase I/II clinical trials, may provide a new approach to cancer therapy based on the accumulation in the mitochondria of the cells of certain carcinomas, for example, those of the colon, breast and pancreas. To support the development of MKT-077 for clinical application as an intravenous (i.v.) therapy, we investigated the metabolic fate of [14C]MKT-077 in BDF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Figure 3A). Care must be taken in interpreting these findings because precursors of JG-98 are known to accumulate at 100-fold higher concentrations in tumor cells in vivo (32). At all three doses, the terminal half-life was calculated to be approximately 20 hours (Figure 4A and Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3A). Care must be taken in interpreting these findings because precursors of JG-98 are known to accumulate at 100-fold higher concentrations in tumor cells in vivo (32). At all three doses, the terminal half-life was calculated to be approximately 20 hours (Figure 4A and Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…MKT-077 was found to be susceptible to rapid metabolism, with a lifetime of only 4.4 Ā± 1.0 min in mouse liver microsomes 21 , largely because of oxidation at the benzothiazole and pyridinium rings 22 . Guided by those studies, we used a previously reported synthetic route (Scheme 1) 14 to generate MKT-077 analogs designed to remove these metabolic liabilities.…”
mentioning
confidence: 99%
“…For example, MKT-077 is rapidly oxidized by liver microsomes (t 1/2~5 min), and it has a short lifetime in mice [154]. Thus, another goal of recent synthetic efforts has been to improve stability.…”
Section: Mkt-077mentioning
confidence: 98%